Influenza vaccine effectiveness: Maintained protection throughout the duration of influenza seasons 2010–2011 through 2013–2014 - Radin, Jennifer M.; Hawksworth, Anthony W.; Myers, Christopher A.; Ricketts, Michelle N.; Hansen, Erin A.; Brice, Gary T. (Vaccine, 2016)
Factors, such as age, comorbidities, vaccine type, herd immunity, previous influenza exposure, and antigenic shift may impact the immune response to the influenza vaccine, protection against circulating strains, and antibody waning. Evaluating vaccine effectiveness (VE) is important for informing timing of vaccine administration and evaluating overall vaccine benefit. VE was assessed using febrile respiratory illness surveillance among Department of Defense non-active duty beneficiaries from influenza seasons 2010–2011 through 2013–2014. Respiratory specimens were taken from participants meeting the case definition and tested by polymerase chain reaction for influenza. VE was calculated using logistic regression and by taking 1 minus the odds ratio of being vaccinated in the laboratory confirmed positive influenza cases versus laboratory confirmed negative controls. This study included 1486 participants. We found an overall adjusted VE that provided significant and fairly consistent protection ranging from 54% to 67% during 0–180days postvaccination. This VE dropped to −11% (95% confidence interval: −102% to 39%) during 181–365days. Our study found moderate VE up to 6months postvaccination. Since the influenza season starts at different times each year, optimal timing is difficult to predict. Consequently, early influenza vaccination may still offer the best overall protection.